Anomalous dielectric constant and AC conductivity in mixed transition-metal-ion xFe2O3-(20 - x)MnO2-80TeO2 glass system - Hisam, Rosdiyana; Yahya, Ahmad Kamal; Mohamed Kamari, Halimah; Talib, Zainal Abidin; Yahaya Subban, Ri Hanum (American Scientific Publishers, 2016)
Glasses with xFe2O3–(20−x)MnO2–80TeO2 (x=2, 5, 10, 15, and 20 mol%) composition were prepared by meltquenching technique to investigate the effects of mixed-transition metal ion Fe2 +/3 +//Mn3 +/4 + on AC conductivity and dielectric properties using impedance spectroscopy. Dielectric constant showed strong variation with Fe2O3 at a frequency ≥10 kHz, where έ decreased to a minimum value at x =10 mol% before increasing for x> 10%. The decrease in έ may be attributed to some form of hindrance effect on heavy dipoles caused by the mixed transition-ion effect (MTE). Meanwhile, variation of AC conductivity with Fe2O3 showed non-linear increase for x ≤ 10 mol% before dropping to a minimum at 15 mol% Fe2O3. This result was attributed to Anderson localization because of the disorder in the glass system. Conductivity analysis showed that the conduction mechanism at the dispersion region for x = 2 mol% followed the correlated barrier hopping (CBH) model, while the mechanism transformed to the overlapping large polaron tunnelling (OLPT) model at higher Fe2O3, content (x > 2 mol%). The electric modulus of the investigated samples showed asymmetric peak of the imaginary part of electric modulus (M¢¢), which reflected a non-Debye type relaxation.